2018
DOI: 10.1007/s11239-018-1662-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in PARK2 and MRPL37 are associated with higher risk of recurrent venous thromboembolism in a sex-specific manner

Abstract: Recent studies indicate that mitochondrial DNA (mtDNA) dysfunction is a biomarker of oxidative stress and can predict the risk of cardiovascular diseases (CVDs). Genetic variants in PARK2 (rs4708928) and MRPL37 (rs10888838) genes have been shown to be associated with altered levels of mtDNA in a sex-specific manner. However, the role of these genetic variants in risk assessment of recurrent venous thromboembolism (VTE) is unknown. We investigated the role of these polymorphisms in VTE recurrence in patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Similarly, PAI-1 polymorphism has been reported by us to be associated with an increased risk of VTE recurrence in the presence of FVL [35]. We have recently shown an association between risk of VTE recurrence and SNPs in mitochondrial regulating genes, suggesting a potential role of mitochondrial function in VTE [36]. Mitochondrial transcription factor A ( TFAM ) has been shown to be involved in mitochondrial biogenesis that in turn affects inflammation; a well-known mechanism in thrombosis [3739].…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, PAI-1 polymorphism has been reported by us to be associated with an increased risk of VTE recurrence in the presence of FVL [35]. We have recently shown an association between risk of VTE recurrence and SNPs in mitochondrial regulating genes, suggesting a potential role of mitochondrial function in VTE [36]. Mitochondrial transcription factor A ( TFAM ) has been shown to be involved in mitochondrial biogenesis that in turn affects inflammation; a well-known mechanism in thrombosis [3739].…”
Section: Discussionmentioning
confidence: 70%
“…Cri-du-chat syndrome [36] MRPL37 mL37 Venous thromboembolism [37] MRPL38 mL38 Liver cancer [38] MRPL39 mL39 Gastric cancer [39] ↓ MRPL40 mL40 Schizophrenia [40][41][42] ↓…”
Section: Mrpl36 Bl36mmentioning
confidence: 99%
“…mrpl16 has been shown to be significantly associated with septic cardiomyopathy [17]. The genetic variation in MRPL37 was linked to an increased risk of venous thromboembolism recurrence [37]. Meng et al designed the cardiac hypertrophy cells by culturing the cardiac cells with 25 mmol/L D-glucose for 48 h. With the help of quantitative real-time PCR, it was confirmed that the expressions of mrpl50, mrps2 and mrps21 were upregulated, and mrpl34 was downregulated [33].…”
Section: Mrps and Heart Diseasesmentioning
confidence: 99%
“…For example, ribosomal protein S6K1 and SLFN14 are present in circulating platelets and exert their unique effects in the process of hemostasis and thrombosis [ 21 , 22 ]. The polymorphism of ribosomal protein MRPL37 predisposes to recurrent venous thromboembolism [ 23 ]. In our study, the Hub genes RPS27A, MRPL13, RPL9, RPS23, and RPS24 belong to the ribosomal protein family.…”
Section: Discussionmentioning
confidence: 99%